Violência no trabalho e as repercussões para a saúde psíquica do trabalhador: estudo sobre o vivido no Sistema Único de Assistência Social - Ana Paula Dias Guimarães (2018)
This study studied the violence in the work experienced in the Sistema Único de Assistência Social- SUAS and its repercussions on the psychic health of the worker, from the perspective of the workers lived in a capital of the southeastern region of Brazil, in the period of August, 2016 to July, 2018. Phenomenology was used as research methodology. In-depth interviews were conducted with 12 workers, who have worked or acted for at least one year in the supervisory role of the municipal management body of SUAS. The collected data were organized in a unit of signification and enunciated by the theoretical reference of Mental Health and Work. The results showed that there are elements of local violence, relationships and organization of work, institutional violence and conflicts in the relationship with the Justice System. The repercussions of these violence on the psychic health of the worker and that gain materiality in the act of working were expressed in psychic suffering, manifested in symptoms such as crying, irritation, sadness, fatigue, fatigue, boredom, uncertainties, helplessness, fear, anxiety, frustration, hypertension, body aches, sleep disorders, mood and eating. Added to the involuntary contamination of the lunch time, rest and leisure of the worker. Of the 12 participants in study 9, they had symptoms compatible with Burnout syndrome. The use of medication and psychoactive substances were reported by 7 workers. In the 12 interviews, it was possible to relate the psychological repercussions to the health of the worker with the situation of violence experienced at work. In addition to the health implications of the worker, there are damages caused to SUAS in terms of quality of work and delivery of the social assistance policy for the user and in the institution such as absenteeism, withdrawal from work, turnover and social-functional follow-up. It is considered the need for urgent intervention of the public power to modify and improve working conditions in SUAS.